Aging between Participation and Simulation - Haltaufderheide, Joschka; Hovemann, Johanna; Vollmann, Jochen (De Gruyter, 2020)
This publication aims to initiate an interdisciplinary discourse on the ethical, legal, and social implications of socially assistive technologies in healthcare. It combines practically relevant insights and examples from current research and development with ethical analysis to uncover moral pitfalls at the intersection between the promotion of social participation and well-being, and risks that may diminish the achievement of these ends.